Fermi-LAT Gamma-Ray Variability Study of Misaligned AGN - Grandi P.; Torresi E.; De Rosa A.; Rainó S.; Malaguti G. (EPJ Web of Conferences, 2013)
We review the gamma-ray variability properties of AGN with a jet not directly pointing at the observer, i.e. Misaligned AGN. This class is mainly populated by nearby low power radio galaxies (i.e. FRIs). The high power radio sources (i.e. FRIIs) are indeed rare in the GeV sky. Our Fermi-LAT inspection of 4 years of data reveals different temporal behaviors, supporting the idea that beaming/jet structural differences could characterize the FRI-FRII jets. The case of 3C111 (FRII) and NGC6251 (FRI) are treated in detail. New insights into the location and dimension of the gamma-ray dissipation regions are provided for galaxies with different radio morphologies.